SPECTRUM OF RHEUMATOID ARTHRITIS PATIENTS PRESENTING TO A TERTIARY CARE HOSPITAL IN PAKISTAN - khan, Muhammad; Mushtaq, Muhammad Salman; Salim, Babur; Mushtaq, Sumera; Gul, Haris; Samreen, Saba (Pakistan Armed Forces Medical Journal, 2021)
Objective: To describe the demographic, clinical, serological and radiological scores in patients with rheumatoid arthritis (RA) presenting in a tertiary hospital in Pakistan.Study Design: Cross sectional study.Place and Duration of Study: Department of Rheumatology, Fauji Foundation Hospital (FFH), Rawalpindi, from Sep 2018 to Feb 2019.Methodology: The study included 52 female patients with RA between the ages of 18 and 80 years. Data were obtained from FFH Rawalpindi's outpatient department. Demographic details, reference data, and serological status were recorded. The joints involved in the onset of the disease, joint deformities, clinical disease activity index (CDAI) and overall functional status were evaluated. Extra-articular manifestations of rheumatoid arthritis have also been examined during a detailed physical examination. The patient's bone mineral density was calculated by the use of dual energy absorptiometry (DEXA scan). Radiological scores were evaluated using modified sharp score.Results: Mean age of the patient was 55.08 ± 8.79 and mean duration of disease 9 .73 ± 7.54. The most common co-morbidity in rheumatoid arthritis patients was hypertension 20 (38.5%). Twenty four (11.7%) patients had osteoporosis. Wrist was the first joint involved in 17 (32.7%) patients. Ulnar deviation was the most common deformity in 12 (23.1%) patients. Sharp score for joint space narrowing was 61.09 ± 36.90 and sharp score joint erosions were 36.90 ± 42.41. Most common extra articular manifestation was anemia.Conclusion: Rheumatoid arthritis as a variable spectrum of disease with different manifestations. Patients had radiological damage as demonstrated by high sharp score even before starting.................